Salt loading with unilateral nephrectomy accelerates decline in glomerular filtration rate in the hypertensive, obese, type 2 diabetic SDT fatty rat model of diabetic kidney disease. (4th February 2022) - Shinozaki, Yuichi; Katayama, Yuko; Yamaguchi, Fuminari; Suzuki, Tomohisa; Watanabe, Kana; Uno, Kinuko; Tsutsui, Takahiro; Sugimoto, Miki; Shinohara, Masami; Miyajima, Katsuhiro; Ohta, Takeshi
Abstract: For the evaluation of novel therapeutic agents for diabetic kidney disease (DKD), it is desirable to examine their efficacy in animal models by using the glomerular filtration rate (GFR) as an index. For this purpose, animal models that demonstrate a short‐term GFR decline because of disease progression are required. Therefore, we aimed to develop such an animal model of DKD by using obese type 2 diabetic spontaneously diabetic Torii (SDT) fatty rats treated with salt loading by drinking water containing sodium chloride with or without unilateral nephrectomy. As a result, we have found that 0.3% salt loading with unilateral nephrectomy or 0.8% salt loading alone caused a rapid GFR decline, hypertension and rapid development of tubulointerstitial fibrosis. Moreover, the addition of losartan to a mixed diet suppressed the GFR decline in SDT fatty rats treated with 0.3% salt loading with unilateral nephrectomy. These results suggest that the model of SDT fatty rats treated with 0.3% salt loading and unilateral nephrectomy could be used as a hypertensive DKD model for evaluating therapeutic agents based on suppression of GFR decline.